Franklin's class trip - Bourgeois, Paulette; Jennings, Sharon; Clark, Brenda (New York : Scholastic, 1999)
Franklin has a good time at the museum especially when he finds out that the dinosaurs are not alive.
310
Keywords: Turtles -- Fiction; School field trips -- Fiction; Dinosaurs -- Fiction